Interpretation in wildlife tourism : assessing the effectiveness of signage to modify visitor’s behaviour at a seal watching site in Iceland - Marschall, Sarah, 1990- (2015)
Læst til 15.6.2016 The effectiveness of signage to modify visitor’s behaviour to reduce negative impacts on wildlife was assessed at a seal watching site on Vatnsnes, NW-Iceland. 2440 visitors were observed and their behaviour recorded from July to September 2014. To test whether type of information has an influence on behaviour, visitors were provided with either deontological (instructions without explanations) or teleological (instructions with explanations) signs, while no signs were provided for the control group. Regression analysis and χ2-tests were used for the analysis. Additionally, the proportion of visitors reading the signs was investigated (1081 observations). The results showed that most of the time visitor’s behaviour improved with having signs and that sometimes the teleological signs were more effective than the deontological ones. However, group type often had a significant influence on the behaviour, with families having the most intrusive behaviour compared to singles, couples and other groups. More than a third (37.7%) of the visitors did not look at the signs and 42.6% stopped at the sign for more than three seconds. Possible improvements of the signs’ design are discussed. From these results, the conclusion is drawn that it is advisable to use teleological signs because they are at least as effective as deontological signs and in some cases they are more effective. Even though signage had a positive influence on the visitor’s behaviour, additional management strategies are presented because it is not clear whether signage on its own is sufficient in reducing disturbance on the seals.